2022
DOI: 10.1109/rbme.2021.3078190
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Wearable Interfaces and Algorithms for Hand Gesture Recognition: A Survey

Abstract: Hands are vital in a wide range of fundamental daily activities, and neurological diseases that impede hand function can significantly affect quality of life. Wearable hand gesture interfaces hold promise to restore and assist hand function and to enhance human-human and human-computer communication. The purpose of this review was to synthesize current novel sensing interfaces and algorithms for hand gesture recognition, and the scope of applications covers rehabilitation, prosthesis control, sign language rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 220 publications
(203 reference statements)
1
58
0
Order By: Relevance
“…[68] More information can be found in other references. [38,69,70] 2.1.2. Hierarchical Cluster Analysis Hierarchical cluster analysis (HCA) is an unsupervised algorithm of multivariate analysis for clustering, including two types: agglomerative (bottom-up approach) and divisive (top-down approach).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…[68] More information can be found in other references. [38,69,70] 2.1.2. Hierarchical Cluster Analysis Hierarchical cluster analysis (HCA) is an unsupervised algorithm of multivariate analysis for clustering, including two types: agglomerative (bottom-up approach) and divisive (top-down approach).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Furthermore, we considered the feature values of sEMG signals as input channels. In previous studies, we discovered that the feature values can be used to improve estimation accuracy during the training process [11,12]. A common problem that occurs when using fewer sensor inputs is insufficient gait information during the gait cycle, which affects the estimation accuracy [7].…”
Section: Normal Gait Cyclementioning
confidence: 99%
“…Recent studies have shown that sEMG is often used during rehabilitation because of its noninvasiveness. It does not involve any pain and discomfort and can be easily applied to the skin [10][11][12]. However, each person has different sEMG patterns.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, hand gesture recognition has been increasingly investigated by both academia and industry, following the versatility and easiness of its implementation. Indeed, thanks to technology progresses in the electronics fields, the recognition of hand movements can be now performed directly with body sensors [1], without the needing of a complex equipment, making it one of the best candidates for Human-Machine Interface (HMI) systems.…”
Section: Introductionmentioning
confidence: 99%